Experimental and numerical investigation of crack propagation and dynamic properties of rock in SHPB indirect tension test - Ai, Dihao; Zhao, Yuechao; Wang, Qifei; Li, Chengwu (International journal of impact engineering, 2019)
•The relationship of dynamic mechnical properties and crack propagation process of rock under SHPB loading has been explored.•A new calculation method of crack propagation velocity was proposed and crack propagation features were analyzed.•Based on Peridynamic thoery, a numerical model for rock material with BD configuration under SHPB test was proposed. To explore the dynamic mechanical properties and crack propagation law of rock under high strain rate impact loading, an experimental investigation with 12 sets of Brazilian disk (BD) rock specimens under Split Hopkinson Pressure Bar (SHPB) loading was undertaken. Unlike the previous researches that study the dynamic mechanical properties and crack propagation law individually, the relationship of them has also been investigated and discussed. More specifically, a dynamic resistance strain gauge and a high-frame camera were employed to simultaneously record stress wave data and rock destruction process videos under different impact velocities. Based on image processing technique, a new calculation method of crack propagation velocity was proposed and then the stress-strain characteristics and crack propagation features were analyzed. The experimental results indicate that: (1) Crack propagation rate of the crack along X-Y direction both rises with the impact velocity increase; (2) the strain of rock along the loading axis is much larger than the vertical direction; (3) there is a certain quantitative relationship between the stress-strain state and the crack area of the rock specimen after it has been damaged. Finally, a numerical model based on Peridynamic theory was developed to simulate crack propagation and dynamic constitutive relationship of rock materials with BD configuration in indirect tension test under SHPB loading, and further reveal the fracture behavior and mechanism of rock materials under high strain rate loading.